2019
DOI: 10.15226/jnhfs.2019.001158
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Obesity Effect of Kaempferia Parviflora (KP) is Attributed to Leptin in Adipose Tissue

Abstract: Kaempferia parviflora (KP) (black ginger) is a plant in Thailand known historically as Kurachai Dam. It belongs to the ginger family and was used as a remedy medicine. Its rhizomes were used to improve obesity, blood flow, inflammation, allergy, and gastrointestinal disorders. However, the mechanism of its anti-obesity effect has not been elucidated. In this study, our purpose was to explore the visceral fat reduction mechanism of KP in vivo. Five weeks old C57BL/6J male mice were used. The mice were fed for 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
2
1
Order By: Relevance
“…However, KPE did not prevent reductions in adiponectin concentrations caused by a HFD. These results are different from previous studies in which KP decreased leptin and increased adiponectin in obese or HFD animal models ( 11 , 31 , 36 , 37 ). The immune system is strongly influenced by leptin’s strong pro-inflammatory effects, and leptin can be secreted by immune stimuli, such as interleukin (IL)-1, IL-6, lipopolysaccharide (LPS), or bacterial infection.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, KPE did not prevent reductions in adiponectin concentrations caused by a HFD. These results are different from previous studies in which KP decreased leptin and increased adiponectin in obese or HFD animal models ( 11 , 31 , 36 , 37 ). The immune system is strongly influenced by leptin’s strong pro-inflammatory effects, and leptin can be secreted by immune stimuli, such as interleukin (IL)-1, IL-6, lipopolysaccharide (LPS), or bacterial infection.…”
Section: Discussioncontrasting
confidence: 99%
“…The KPE-treated groups demonstrated a decrease in BW gain, body fat mass, adipose tissue weight, adipocyte size, and serum levels of glucose, insulin, TG, cholesterol, and leptin. Several recent studies demonstrated that KPE activates brown adipose tissue and increases energy expenditure, resulting in a preventive effect on obesity ( 11 , 22 , 26 ). In addition to this, studies to reveal the mechanism of the anti-obesity effect of KPE are being actively conducted recently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation